2000
DOI: 10.4049/jimmunol.165.12.7133
|View full text |Cite
|
Sign up to set email alerts
|

Vγ9Vδ2 T Cells Impair Intracellular Multiplication ofBrucella suisin Autologous Monocytes Through Soluble Factor Release and Contact-Dependent Cytotoxic Effect

Abstract: Human Vγ9Vδ2 T cells are considered to play an important role in brucellosis, as this population is dramatically increased in peripheral blood of patients during the acute phase of the infection. This T lymphocyte population has been largely demonstrated to be activated by small m.w. nonpeptidic molecules from natural or synthetic origin. We recently identified a nonpeptidic fraction of Brucella suis that specifically activates human Vγ9Vδ2 T cells. Using a two-separate-chambers system, we showed that Brucella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 57 publications
0
55
0
1
Order By: Relevance
“…Ottones et al [66] reported morphological changes of monocytes co-cultured together with activated Vc9/Vd2 T cells yet did not characterize those activated monocytes in more detail. Other studies showed an induction of CD40, high-mobility group box 1 protein (HMGB-1) and tissue factor (TF) by monocytes in PBMC cultures treated with IPP or zoledronate [67,68].…”
Section: Differentiation Of Monocytes: Local Generation Of Inflammatomentioning
confidence: 99%
“…Ottones et al [66] reported morphological changes of monocytes co-cultured together with activated Vc9/Vd2 T cells yet did not characterize those activated monocytes in more detail. Other studies showed an induction of CD40, high-mobility group box 1 protein (HMGB-1) and tissue factor (TF) by monocytes in PBMC cultures treated with IPP or zoledronate [67,68].…”
Section: Differentiation Of Monocytes: Local Generation Of Inflammatomentioning
confidence: 99%
“…Also, it is reported that bacillus Calmette-Guérin vaccine application can exhibit significantly beneficial effect in controlling the malignancy, in particular the bladder cancers (41,42). Because many microbes are indicated to produce and secrete nonpeptide Ags for human ␥␦ T cells such as alkyl pyrophosphates and alkyl amines (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), it is tempting to speculate that these microbial nonpeptide Ags may contribute to the restriction of growth of incidental tumor cells via stimulation of ␥␦ T cells to proliferate and produce IFN-␥ as well as sensitization of the tumor cells for the ␥␦ T cell-mediated cytotoxicity. Our recent report suggested that ␥␦ T cells might provide innate immunity in patients with renal cell carcinomas, implicating a possible link between tumor immunity and urinary infections (56).…”
Section: Discussionmentioning
confidence: 99%
“…(E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate immunotherapeutics ͉ lung ͉ macaques ͉ immune regulation ͉ clonal expansion A ccumulating evidence suggests that human V␥2V␦2 (also called V␥9V␦2) T cells may play a role in mediating immunity against microbial pathogens (1)(2)(3)(4)(5)(6)(7)(8). V␥2V␦2 T cells constitute 60-95% of circulating human ␥␦ T cells and are unique in their ability to massively expand during various bacterial and protozoal infections (9).…”
Section: The Possibility That V␥2v␦2 T Effector Cells Can Confer Protmentioning
confidence: 99%